8-isopentenyl isoflavone derivatives from the whole herb of Sphaerophysa salsula. Issue 21 (2nd November 2018) - Jiao, Li-Jin; Wang, Wei-Dong; Tao, Yan-Duo; Shao, Yun; Mei, Li-Juan; Liu, Zeng-Gen; Wang, Qi-Lan; Dang, Jun
Abstract: Phytochemical studies on the whole herb of Sphaerophysa salsula has resulted in the discovery of one new 8-isopentenyl isoflavone derivative, named sphaerosin s2 (3-(8-(2-hydroxypropan-2-yl)-3, 4-dihydro-2 H -furo[2, 3- h ]chromen-3-yl)-2, 6-dimethoxyphenol) (1 ), along with four know 8-isopentenyl isoflavone derivatives (2 –5 ). Compounds (2, 4 and5 ) were isolated for the first time from this species. Their structures were elucidated on the basis of ESI-MS, UV, IR, 1D NMR and 2D NMR data. Abstract :